2019
DOI: 10.1017/s1368980018003804
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the restaurant consumer food environment in Rochester (NY, USA) and London (ON, Canada): assessing children’s menus by neighbourhood socio-economic characteristics

Abstract: Objective: To assess restaurant children's menus for content and nutritional quality; and to investigate the relationship between the restaurant consumer food environment for children and neighbourhood-level socio-economic characteristics within and between one Canadian city and one US city. Design: Cross-sectional observational study. Setting: London, ON, Canada and Rochester, NY, USA. Participants: Restaurant children's menus were assessed, scored and compared using the Children's Menu Assessment tool. We qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 51 publications
1
11
1
Order By: Relevance
“…To our knowledge, the present analysis is the first to examine the association between consumer food environment in HC restaurants and neighborhood characteristics. The few studies that have examined restaurants adjusting for neighborhood characteristics showed that low area income and high proportion of minority populations were significantly associated with lower healthy food availability [ 16 , 17 , 19 , 20 ]. Our research did not find significant differences in the healthfulness of the consumer food environment in HC restaurants by area Hispanic composition, as measured by the NEMS-R.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, the present analysis is the first to examine the association between consumer food environment in HC restaurants and neighborhood characteristics. The few studies that have examined restaurants adjusting for neighborhood characteristics showed that low area income and high proportion of minority populations were significantly associated with lower healthy food availability [ 16 , 17 , 19 , 20 ]. Our research did not find significant differences in the healthfulness of the consumer food environment in HC restaurants by area Hispanic composition, as measured by the NEMS-R.…”
Section: Discussionmentioning
confidence: 99%
“…The total score of the adapted NEMS-R (NEMS-HCR) has the potential to range of –7 to 22, where higher scores denote healthier consumer nutrition environments. As the score has not been divided into meaningful evidence-based categories [ 10 ], we used natural breaks (also known as “Jenks”) to categorize the consumer nutrition environment scores in HC restaurants into three categories (low, medium, high) to be able to compare restaurants [ 17 ]. This approach was used, as opposed to the more commonly used tertiles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nutritional health of adolescents is a growing public health concern in many developed countries, as an estimated one-quarter to one-third of teenagers in high-income countries such as Australia, Canada, Ireland, New Zealand, the United Kingdom and the United States, are currently living with overweight or obesity [5,6,7]. An increasing body of literature recognizes the health impacts of food environments (FEs) [8,9,10], which are defined as the surroundings and conditions affecting one’s dietary patterns and nutritional health outcomes [11]. Studies have shown that youth’s FEs can be highly obesogenic, as they tend to lack easily accessible, nutritious food options, and expose teens to a wide selection of energy-dense, nutrient-poor foods [12,13].…”
Section: Introductionmentioning
confidence: 99%